Omadacycline for the treatment of severe pneumonia caused by Chlamydia psittaci complicated with acute respiratory distress syndrome during the COVID-19 pandemic - Wang, Dao-Xin; Xiao, Ling-Xi; Deng, Xin-Yu; Deng, Wang (Frontiers in Medicine, 2024)
Introduction Chlamydia psittaci infection in humans is a rare cause that mainly present as community-acquired pneumonia. Severe Chlamydia psittaci pneumonia can lead to acute respiratory distress syndrome (ARDS), septic shock, or multiple organ dysfunction with a mortality rate of 15%–20% before accurate diagnosis and targeted treatment. Metagenomic next-generation sequencing (mNGS) has an advantage in achieving early diagnosis. In the study, omadacycline implementation was described to provide a better understanding of effectiveness in severe psittacosis pneumonia with ARDS. Methods Sixteen patients with severe psittacosis pneumonia with ARDS were selected between September 2021 and October 2022. They were diagnosed using mNGS and treated with omadacycline. Retrospective analysis of clinical manifestations, laboratory data, disease progression, diagnostic tool, treatment, and prognosis was summarized. Results Common symptoms included fever, dyspnea, and cough. All patients developed ARDS, accompanied by septic shock (43.7%) and pulmonary embolism (43.7%). Laboratory data showed normal leucocytes, increased creatine kinase isoenzyme, and decreased albumin with liver dysfunction in most patients. All patients had increased neutrophils, C-reactive protein, procalcitonin, and D-dimer with decreased lymphocytes. Airspace consolidation, ground glass opacity, and pleural effusion were found on chest CT. mNGS results were obtained in 24–48 h to identify the diagnosis of Chlamydia psittacosis. All patients received mechanical ventilation with omadacycline treatment. Fourteen patients experienced complete recovery, while the other two patients died from multidrug-resistant bacterial infection and renal failure. Conclusion mNGS has a significant value in the diagnosis of Chlamydia psittaci infection. Timely treatment of omadacycline can improve prognosis and provide a promising new option for the treatment of severe Chlamydia psittaci pneumonia with ARDS.